2014
DOI: 10.1063/1.4888564
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the dynamics of flexible Lennard-Jones chains

Abstract: The isomorph theory provides an explanation for the so-called power law density scaling which has been observed in many molecular and polymeric glass formers, both experimentally and in simulations. Power law density scaling (relaxation times and transport coefficients being functions of ρ γ S /T , where ρ is density, T is temperature, and γS is a material specific scaling exponent) is an approximation to a more general scaling predicted by the isomorph theory. Furthermore, the isomorph theory provides an expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 75 publications
7
64
0
Order By: Relevance
“…In the MD study the polymer chain is modelled with either rigid or semi-rigid bonds. The variant of the polymer model with semi-rigid bonds, differently from the one with rigid bonds [90], is not a strongly-correlating liquid, as previously noted [27] and recently reported [28] for a closely related model, owing to the competition between the bonding and the non-bonding interactions [25,26]. This means that there is no effective inverse-power law potential replacing the actual particle-particle interaction potential, thus precluding the usual TS interpretation.…”
Section: Introductionmentioning
confidence: 82%
“…In the MD study the polymer chain is modelled with either rigid or semi-rigid bonds. The variant of the polymer model with semi-rigid bonds, differently from the one with rigid bonds [90], is not a strongly-correlating liquid, as previously noted [27] and recently reported [28] for a closely related model, owing to the competition between the bonding and the non-bonding interactions [25,26]. This means that there is no effective inverse-power law potential replacing the actual particle-particle interaction potential, thus precluding the usual TS interpretation.…”
Section: Introductionmentioning
confidence: 82%
“…with either purely repulsive or attractive interactions as one approaches the glass transition. [12][13][14][15][16][17][18][19] Common to all computational studies, the nature of the interactions is at the core of their ability to adequately probe polymeric properties. Therefore accessing the basic assumption that polymer chains can be described solely by repulsive interactions is one critical aspect of probing polymers computationally.…”
mentioning
confidence: 99%
“…This fact is not reliant on a particular form of the potential as long as the system has strong virial potential-energy correlations at the state points in question. 28 In particular, it is not restricted to inverse-power potentials or even to pair potentials, and several molecular systems have been shown to conform to the isomorph theory in computer simulations 32,33 and experiments. [34][35][36] Not all systems have isomorphs, though.…”
mentioning
confidence: 99%
“…31,44 For such systems, the scaling property is rarely obvious from the mathematical expression for U(R) for which reason the term "hidden scale invariance" is sometimes used. 28,33,[45][46][47][48][49] The R-simple region of a given system is identified in computer simulations as the state points characterized by strong virial potential-energy correlations in constant-volume canonical-ensemble fluctuations. 28,50,51 For the LJ liquid, our simulations have shown that the Pearson correlation coefficient obeys R > 0.94 at all state points with density and temperature higher than those of the liquid at the triple point.…”
mentioning
confidence: 99%